Analysis of Ustadz Das'ad Latif's Language Style in Delivering Dakwah Via Youtube - nur rovida femila sari; Luluk Ilma Inun; Luluk Fikri Zuhriyah (UIN Fatmawati Sukarno Bengkulu, 2025)
Da'wah is a very important part of Islam. A preacher should be someone who studies and knows how to preach, especially in the style of preaching language. The style of a preacher influences the interest of the listener, so a different delivery style is needed. This paper examines the style of language in Ustaz Das'ad Latif's lectures on his Youtube channel. Ustaz Das'ad Latif is famous for his relaxed lecture method and funny stories. Ustaz Da'as Latif's delivery of da'wah uses light, clear, and firm communication. The purpose of this study is to analyze the style of language in Ustaz Das'ad Latif's lectures on Youtube. The theory used in this study is language style according to Gorys Kaeraf. This study uses a qualitative method with a descriptive approach. Data were obtained from documentation in the form of journals, theses, theses and other literature sources. Analysis was carried out on data that had been described based on the theory used. The results of the study show that Ustaz Das'ad Latif applies language style based on word choice, tone and sentence structure. However, the most prominent style of preaching language uses informal language style and conversational language style. The use of a spirited and humorous tone is the uniqueness of Ustaz Das'ad Latif. While the sentence structure is conveyed through the beginning of the phrase and repetition of words.